2022
DOI: 10.3389/fpubh.2022.831424
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Week Game-Based School Intervention Improves Physical Fitness in 12–14-Year-Old Girls

Abstract: The aim of this study was to determine the effects of a twelve-week game-based school intervention on physical fitness in girls aged 12–14 years. Fifty-nine adolescent girls (13.2 ± 0.3 years) were randomly assigned to a group that participated in a game-based after-school program (EXP) or a control group (CON) that participated only in mandatory physical education. The EXP group had the additional program twice a week after school for 40 min/session for 12 weeks alongside with regular physical education class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Then, the researcher concluded that twelve weeks of game-based training signi cantly affected the endurance performance of male volleyball players. This result is supported by Petrušič et al (2022), who con rmed that game-based training modes in volleyball were effective in improving a range of intermittent endurance indices due to their higher game-based speci city.…”
Section: Discussionmentioning
confidence: 54%
“…Then, the researcher concluded that twelve weeks of game-based training signi cantly affected the endurance performance of male volleyball players. This result is supported by Petrušič et al (2022), who con rmed that game-based training modes in volleyball were effective in improving a range of intermittent endurance indices due to their higher game-based speci city.…”
Section: Discussionmentioning
confidence: 54%
“…This is a positive finding for PE in schools-the current classes were somewhat beneficial to the students. This finding was supported by Cocca, et al [60], Cocca, et al [61], and Petrušič, et al [62] who also found that PE classes, including games, could improve the PF of students.…”
Section: Discussionmentioning
confidence: 59%
“…A total of 3,486 participants (1,685 girls) were included in the control group (CON) group that participated in regular physical activity (PA) or physical education (PE), 426 participants (171 girls) were included in the active video games (AVGs) group ( 24–31 ), 1,670 participants (803 girls) were included in the game-based exercise (GB) group ( 32–42 ), 1,085 participants (522 girls) were included in the high-intensity interval training (HIIT) group ( 36 , 37 , 43–65 ), 1,005 participants (462 girls) were included in the strength training (ST) group ( 41 , 66–82 ), 599 participants (300 girls) were included in the aerobic training (AT) group ( 49 , 53 , 56 , 61 , 62 , 66 , 76 , 83–87 ), and 307 participants (197 girls) were included in the combined aerobic and strength training (CT) group ( 68–71 , 76 , 88 , 89 ). Interventions lasted on average of 13.9 ± 9.6 weeks and ranged from 4 to 50 weeks, with 73% of studies lasting less than 12 weeks.…”
Section: Resultsmentioning
confidence: 99%